Newborn Screening for Krabbe Disease and Other Lysosomal Storage Disorders: Broad Lessons Learned - Joseph J. Orsini; Michele Caggana (MDPI AG, 2017)
Newborn screening (NBS) for Krabbe disease (KD) began in New York (NY) in August 2006. In summary, after eight years of screening there were five infants identified with early-onset Krabbe disease. Four underwent transplant, two are surviving with moderate to severe handicaps, and two died from transplant-related complications. An additional forty-six asymptomatic infants were found to be at moderate or high risk for disease. Screening for KD is both analytically and medically challenging; since screening for KD possesses both of these challenges, and many more, the lessons learned thus far could be used to predict the challenges that may be faced when screening for other lysosomal storage disorders (LSDs). This paper briefly reviews reports of NBS for LSDs from varied world programs. The challenges encountered in screening for KD in NY will be highlighted, and this experience, combined with hindsight, will inform what may be expected in the future as screening for LSDs expands.